2020
DOI: 10.1038/s41598-020-65130-w
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Refractive Error in Millennials

Abstract: over the last decades, the prevalence of myopia has suddenly increased, and at this rate, half of the world's population will be myopic by the year 2050. Contemporary behavioural and lifestyle circumstances, along with emergent technology, are thought to be responsible for this increase. twin studies mostly reported a high heritability of refractive error across ethnicities. However, heritability is a population statistic and could vary as a result of changing environmental conditions. We studied the variance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Most of these studies were conducted either across a general population including all age groups or an old population. Furthermore, none of them captures the environmental changes that have occurred during the last two decades which was evident in a recent work, where heritability of objective refraction in the sample used for the present study was considerably lower compared to a middle-aged twin population from the same geographical origin 26 . Sample characteristics, such as age, years of schooling or geographical area may be responsible for those inconsistencies.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Most of these studies were conducted either across a general population including all age groups or an old population. Furthermore, none of them captures the environmental changes that have occurred during the last two decades which was evident in a recent work, where heritability of objective refraction in the sample used for the present study was considerably lower compared to a middle-aged twin population from the same geographical origin 26 . Sample characteristics, such as age, years of schooling or geographical area may be responsible for those inconsistencies.…”
Section: Introductionmentioning
confidence: 82%
“…A sample from the British population also showed high heritability in a study conducted by Hammond et al 22 (sample age 49 to 79 years) showed heritability of 84%. A comprehensive table of all relevant studies done from 1962 has been provided in our previous work 26 . Most of these studies were conducted either across a general population including all age groups or an old population.…”
Section: Introductionmentioning
confidence: 99%
“…In that study, we found that variance of refractive error, induced by changes in eye size, was mainly in uenced by variance in environmental exposures during ocular development. 24 An extensive SEM analysis of peripheral refraction applied in this sample allowed us to differentiate to which point the variance of refractive error, measured from the LOS up to of up to ± 35 degrees retinal area, was in uenced by variance in genes or childhood visual exposures. The central large environmental in uence found in our study participants may predict a trend of ocular axial length growth limited mainly at the posterior pole of the eyeball, in an area from the optical disk to around 20 degrees temporal, supporting the 'posterior pole elongation' myopia theory.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22][23] In contrast, a recent twin study with a young sample reported a considerably lower heritability estimate in comparison to a middle-aged twin population from the same twin registry. 24 To the best of our knowledge, there is only one published study estimating PR heritability, conducted in 120 Chinese children and adolescents, which reported a signi cant role of additive genetic factors to explain the variance of peripheral refraction, 25 thus supporting a relevant responsibility of genetic variation on myopia development. However, this study was limited in that they only studied peripheral refraction at a single peripheral angle (40° from the fovea), did not provide information about the refractive error at the line of sight (central measurements), and included a wide age span, ranging from children to young adults (8-20 years), with very different levels of physical development and visual need or exposure.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study with twins suggested that refractive error is mostly affected by a shared environment rather than heritability. 4 Other often-mentioned risk factors for myopia development include extensive near work, 5 insufficient outdoor activities in children, 6 and low luminance conditions. 7 …”
mentioning
confidence: 99%